Potential marker subset of blood-circulating cytokines on hematopoietic progenitor-to-Th1 pathway in COVID-19 - Takashima, Yasuo; Inaba, Tohru; Matsuyama, Tasuku; Yoshii, Kengo; Tanaka, Masami; Matsumoto, Kazumichi; Sudo, Kazuki; Tokuda, Yuichi; Omi, Natsue; Nakano, Masakazu; Nakaya, Takaaki; Fujita, Naohisa; et al. (Frontiers in Medicine, 2024)
Herein, we analyzed a relatively large subset of proteins including 109 kinds of blood circulating cytokines and precisely described cytokine storm in the expression level and the range of fluctuations during hospitalization for COVID-19. Of the proteins analyzed in COVID-19, approximately 70% were detected with Bonferroni-corrected significant differences in comparison with disease severity, clinical outcome, long-term hospitalization, and disease progression and recovery. In specific, IP-10, sTNF-R1, sTNF-R2, sCD30, sCD163, HGF, SCYB16, IL-16, MIG, SDF-1, and fractalkine were found to be major components of the COVID-19 cytokine storm. Moreover, M-CSF and sTNF-R2 were constituted of a central hub module in the dense co-expression correlation network of the cytokines. Our finding suggested that 11 cytokines (i.e., SDF-1, SCYB16, sCD30, IL-11, IL-18, IL-8, IFN-γ, TNF-α, sTNF-R2, M-CSF, and I-309) would be associated with the infection, mortality, disease progression and recovery, and long-term hospitalization. Increased expression of these cytokines could be explained in sequential pathways from hematopoietic progenitor cell differentiation to Th1-derived hyperinflammation in COVID-19, which might also develop a novel strategy for COVID-19 therapy with recombinant interleukins and anti-chemokine drugs.